Soziale Frauenpflichten : Vorträge gehalten in deutschen Frauenvereinen - Salomon, Alice, 1872-1948 (Historische Quellen zur Frauenbewegung und Geschlechterproblematik, 1902)
A series of lectures delivered to various German women's groups on the subject of women involved in social or philanthropic work.